The Penitence Narrative in the Life of Adam and Eve - Anderson, Gary A. (Hebrew Union College annual / Jewish Institute of Religion, 1992)
The recent publication of the Armenian and Georgian versions of the Life of Adam and Eve have resulted in an entirely new approach to the study of this document. The new data they provide require that all previous work on this document and its purported Jewish character be rethought. This essay has selected a portion of this narrative, that regarding the penitence of Adam and Eve, as an initial point of entry into the discussion of the document's origin and development. The principal thesis is that the literary theme of Adam and Eve's penitence had to have originated in a Jewish exegetical context. The original contours of this Jewish theme, though present to different degrees in the Latin and Greek versions, is most evident in the Armenian and Georgian material. Later redactions of the narrative tended to obscure the obvious markers of textual exegesis in order to smooth out narrative difficulties and to render the material more amenable to Christian use.